Analisa Kapasitas Jalan Jembatan di Desa Bulukandang – Ketan Ireng Kabupaten Pasuruan - Salsabila, Nisa; ., Khofifah (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
-Transportation is the cornerstone of infrastructure that improves the economy and mobility. Bridge road capacity is aparameter used to assess the dimensional strength of the infrastructure to serve stressful traffic. The aim of the research isto determine the capacity of the bridge road in Bulukandang - Ketan Ireng village, to compare this capacity with thecurrent traffic volume.The Bridge Road Capacity Analysis Study in Bulukandang - Ketan Ireng Village, Pasuruan Regencyused quantitative research using numerical calculations and analyzed statistically based on the 1997 Indonesian RoadCapacity Manual (MKJI).The results of the discussion on the analysis of the capacity of the bridge road in Bulukandang -Ketan Ireng Village are that the capacity of the Bridge Road in Bulukandang - Ketan Ireng Village, Pasuruan Regency is 8- 10 tons. The capacity of the Bridge Road. The traffic volume that occurs on the Bridge Road in Bulukandang - KetanIreng Village occurs on weekends or Saturday afternoons with a total of 154 pcu/hour. Meanwhile, the lowest trafficoccurred in the morning on Monday with a total of 102 pcu/hour